A description of the two-dimensional representations of the dihedral group over the commutative local rings (in Ukrainian) - Yu. V. Petechuk (Математичні Студії)
The full description of the two-dimensional representations ofthe dihedral group $D_{m} =leftlangle a,b{m ; }left|a^{m} =1, b^{2} =1, bab^{-1} =a^{-1} ight. ightangle, $$m>1$ over the commutative local rings, is proposed from thepoint of view of a unified position. The conditions for their irreducibility, indecomposable and equivalency are found.